Woodframe: Light framing houses for developing countries - De Araujo, Victor Almeida; Cortez-Barbosa, Juliana [UNESP]; Garcia, José Nivaldo; Gava, Maristela [UNESP]; Laroca, Christine; César, Sandro Fábio (My University, 2016)
The building technique of light wooden framing, i.e., woodframe, represents a great innovative goal of construction, due to the very efficient levels of rationalization of material, operational flexibility and productive agility. In addition, excessive use of natural materials of renewable character in the woodframes, as the wood of planted forests, contributes to sustainability, a desired factor in most modern homes. In recent years, Latin American countries have suffered from the constant housing deficit, which destroys the possibilities of the first property by the neediest populations. Therefore, it is necessary to propagate studies, research and information on industrialized housing construction techniques, such as woodframe. This study focused on the exhibition by a state of the art of this innovative wooden housing typology, emphasizing its advantages, importance, types, and its current panorama in the regions in development stage, such as Latin American countries. Currently, the woodframe is known as a modern wooden residential technique, and it is conquering the public of all kind of economic classes, because of its innovation, lightness, competitive costs, and also by the efficient levels of sustainability, cleanness, assembly time, and rationalization of raw materials.
Keywords: Dissemination; Light framing; Strategies; Wood-frame; Wooden housing